2018
DOI: 10.1111/echo.14092
|View full text |Cite
|
Sign up to set email alerts
|

Normative reference data, determinants, and clinical implications of right atrial reservoir function in women assessed by 2D speckle‐tracking echocardiography

Abstract: In this cross-sectional trial, we determined reference values, feasibility and reproducibility, clinical and echocardiographic determinants, and possible clinical implications of RA strain analysis. Our data may help to introduce the analysis of RA mechanics into future echocardiographic routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In the context of these two illustrated brief case summaries and the data presented in this issue of the journal by Brand et al, and reports by other investigators referred here, not only the scientific merit of the newly published European Association of Cardiovascular Imaging (EACVI) consensus document standardizing the right ventricular and right atrial strain quantification methods has been relevant, but also the extremely valuable and timely published document should stimulate the clinicians and investigators alike to continue further research in this modern and exciting era of cardiology and cardiac imaging, particularly in atrial fibrillation and heart failure irrespective of reduced or preserved left ventricular ejection fraction. As there are some controversies regarding the precise pathophysiology of HFPEF, right atrial strain at rest or during some forms of stress, pharmacological or physiological, may uncover elevated pressure bilaterally—a prerequisite for the echocardiographic diagnosis of HFPEF in the background of symptoms and elevated NTproBNP.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In the context of these two illustrated brief case summaries and the data presented in this issue of the journal by Brand et al, and reports by other investigators referred here, not only the scientific merit of the newly published European Association of Cardiovascular Imaging (EACVI) consensus document standardizing the right ventricular and right atrial strain quantification methods has been relevant, but also the extremely valuable and timely published document should stimulate the clinicians and investigators alike to continue further research in this modern and exciting era of cardiology and cardiac imaging, particularly in atrial fibrillation and heart failure irrespective of reduced or preserved left ventricular ejection fraction. As there are some controversies regarding the precise pathophysiology of HFPEF, right atrial strain at rest or during some forms of stress, pharmacological or physiological, may uncover elevated pressure bilaterally—a prerequisite for the echocardiographic diagnosis of HFPEF in the background of symptoms and elevated NTproBNP.…”
Section: Resultsmentioning
confidence: 80%
“…For the right atrium, until the writing of this letter, no such meta‐analysis is available. In this issue of echocardiography, Brand et al have reported normal right atrial strain derived from a group of urban females selected from the general population of Berlin, Germany. Mean RA reservoir strain (RAS), RA conduit strain, and contraction strain in this reference group were 44.9 ± 11.6%, 27.1 ± 9.5%, and 17.0 ± 5.9%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference is presumably due to the different ECG gating used in the two studies: A P‐to‐P‐wave gating of the ECG resulted in lower values in the earlier investigation, whereas R‐to‐R gating provided higher values in the later publication. Normal values of RA strain are about to be published …”
Section: Normative Values Of Left and Right Atrial Strainmentioning
confidence: 99%
“…Normal values of RA strain are about to be published. 15 In the backdrop of this brief introduction on 2D-STE, we present some snapshots of LA, RA, and RV strain imaging in various clinical situations.…”
Section: Normative Value S Of Lef T and Ri G Ht Atrial S Tr Ainmentioning
confidence: 99%